Analisis tingkat ketergantungan impor pada industri susu Indonesia - Meuthia Vika Ruccy; Suharno Suharno; Ratna Winandi Asmarantaka (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2022)
The increase in Indonesia’s dairy imports confirms that Indonesia is more dependent on imports. Practically, the bigger import dependence leads to the bigger exposure of import to GDP. The characteristics of imports are also described by the degree of import concentration. These research objectives are: (1) to find out the level of import dependency and the degree of import openness of Indonesian dairy imports; and (2) to find out the import concentration of Indonesian dairy imports based on commodity and geographic concentrations. This study uses the Import Dependency Ratio (IDR) method, the degree of import openness (DKI), the degree of commodity concentration (DKK); and degree of geographic concentration (DKG). This research uses annual time series secondary data in 2014 to 2018 for the dairy HS code as follows: (1) HS 0401, (2) HS 0402, (3) HS 0403, (4) HS 0404, (5) HS 0405, and (6) HS 0406. The results showed Indonesia has a high dependence on dairy products; with an average of 40.42 percent of Indonesia's dairy needs are met from imports. However, the degree of import openness of dairy imports is still relatively low; Indonesian dairy import spends 0.14 percent of Indonesia's GDP. Indonesian dairy imports are relatively distributed in the six dairy HS codes. Geographically, only HS code 0405 imports which are concentrated from one source, specifically from New Zealand. Meanwhile, dairy imports from other HS codes are relatively distributed from various countries.